Telomerase activation by histone deacetylase inhibitor in normal cells - Takakura, Masahiro (Oxford University Press, 2001)
Although telomerase activity is known to be regulated mainly at the level of transcription of the human telomerase catalytic subunit (hTERT) gene, the molecular mechanism underlying tumor-specific expression of telomerase remains unclear. Emerging evidence suggests that reversible acetylation of nucleosomal histones and the resultant changes in the chromatin structure are important processes in gene transcription. In particular, histone deacetylase (HDAC) inhibitors activate the transcription of certain genes by altering the acetylation status of nucleosomal histones. The present study examines the effects of HDAC inhibitor on hTERT gene transcription. Treatment with tricostatin A (TSA) induced significant activation of hTERT mRNA expression and telomerase activity in normal cells, but not in cancer cells. Transient expression assays revealed that TSA activates the hTERT promoter. Furthermore, the proximal 181 bp core promoter of hTERT, which contains two c-Myc and five Sp1 sites, was determined to be the responsible element. Overexpression of Sp1 enhanced responsiveness to TSA, and mutation of Sp1 sites, but not c-Myc sites, of the core promoter of hTERT abrogated this activation. Introduction of the dominant-negative form of the Sp family inhibited TSA activation. These results indicate that HDAC inhibitor activates the hTERT promoter in normal cells, in which Sp1 plays a key role. This finding suggests one way whereby histone deacetylation may be involved in silencing the hTERT gene in normal cells.